Duct fanned shielding design for quadrotors - Balakrishnan, Sethuram (UiT Norges arktiske universitet, 2016)
The master thesis work involved the design implementation of a duct fanned shielding for Quadrotors. This included the investigation of various settings for duct shielding and to identify the best possible option to safe guard propellers of the quadrotor. In addition, the work focused on improving the aerodynamic efficiency, reducing the mass of flight and the use of quadrotors in the arctic region. The first goal was to understand and predict the necessary ways to improve the thrust with minimal increase in the mass of the quadrotor. The second goal was to check the durability of the duct. In the elementary models, the duct was modelled as a rigid mass and preliminary tests were conducted using diverse software. Problems, were found in the core areas which had to be solved, independent of the size and shape of quadrotor. Initially before designing the shielding, preliminary research was incorporated for understanding different aspects of the quadrotor. This report is one such procedure, which focuses on different types of quadrotors, construction styles, market analysis, customer satisfaction, designing and simulation and manufacturing processes. A study of the ducted principle culminates in the development of some simple structures and analysis which may prove useful in practice. Some comparisons between the conceptual models: rectangular concept of connection, aerodynamic concept with 45deg of connection, aerodynamic concept with 60deg of connection and cylindrical concept of connection have been made in order to access their strengths and highlight their various shortcomings. The development of a final duct model for quadrotor shielding is discussed in detail with particular emphasis on thrust improvement (especially design features). A limited study on manufacturing approach has been conducted in order to gain some insight into the production equipment and to follow the evolution of the product. Future work in this area is indicated although the product is only for research purpose.